(untitled) (Journal of Psychiatrists’ Association of Nepal, 2025)
Background: Sleep is an integral part of human biological rhythm and it is essential for optimal health as well as cognitive and psychosocial functioning. WHO has recognized sleep as a global health issue of the 21st Century. Sleep problems may lead to physical & mental health, educational and societal problems which is need to be a concern. This study aimed to assess the factors associated with quality of sleep and to identify the level of sleep quality among undergraduate nursing students of Biratnagar nursing campus. Methods and Materials: A cross-sectional study was conducted among 314 nursing students studying at Biratnagar nursing campus. The purposive sampling technique was adopted to obtain the desired sample size. Data entry and analysis were done in SPSS version 16. Descriptive statistics like mean, proportion, standard deviation and inferential statistics like bivariate regression were used. All estimates were presented with a 95% Confidence Interval (CI). Findings were presented in table. Results: The prevalence of poor sleep quality was nearly half (48.8%). Nearly half of the nursing students had poor sleep quality with a PSQI total average score found at a higher level >5. The mean total PSQI score of nursing students was 5.98±3.31. The study showed a significant association of sleep quality with educational status (p=0.030) and presence of mental illness (p=0.042). Conclusion: These study findings concluded that nearly half of the nursing students had poor sleep quality. Thus sleep hygiene awareness and interventions are needed to initiate among young nursing students to achieve optimum level of health and good academic performance.